THE USE OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN IMPROVING STUDENTS’ LEARNING OUTCOME OF IPS FOR FOURTH GRADE STUDENTS OF SD NEGERI KEMIRI KIDUL IN THE ACADEMIC YEAR OF 2016/2017 - Faedoni, Bangkit Yogi; Suripto, Suripto; Rokhmaniyah, Rokhmaniyah (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: THE USE OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN IMPROVING STUDENTS? LEARNING OUTCOME OF IPS FOR FOURTH GRADE STUDENTS OF SD NEGERI KEMIRI KIDUL IN THE ACADEMIC YEAR OF 2016/2017. The objective of this research is to improve learning outcome of students through the use of contextual teaching and learning (CTL) for fourth grade students of sd negeri kemiri kidul in the academic year of 2016/2017. This research is a collaborative Classroom Action Research (CAR). Subjects of the research were 18 students of the fourth grade of SD Negeri Kemiri Kidul. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptiveanalysis consisting of data reduction, data display, and drawing conclusion or verification. The result of this research is the use of Contextual Teaching and Learning  (CTL) can improve students? learning outcome of IPS for fourth grade students of SD Negeri Kemiri Kidul.Keywords: contextual teaching and learning  (ctl), learning outcome, IPS